Endogenous tachykinins facilitate transmission through parasympathetic ganglia in guinea-pig trachea. - Watson, N. (Nature Publishing Group, 1993)
1. Exogenous and endogenous tachykinins facilitate cholinergic nerve-induced bronchoconstriction in guinea-pig. Using a vagally innervated guinea-pig tracheal tube preparation we have investigated the involvement of endogenous capsaicin-sensitive neuropeptides in both pre- and postganglionic cholinergic neurotransmission. The effects of the neutral endopeptidase inhibitor (NEP), phosphoramidon, were investigated in this preparation either alone or in conjunction with sensory neuropeptide depletion by capsaicin pretreatment. The subtype of neurokinin receptor mediating this facilitatory effect of tachykinins has also been examined, by the use of selective tachykinin receptor agonists and a selective NK1 receptor antagonist. 2. Cholinergic contractions of the sealed Krebs filled tracheal tube preparation were recorded as increases in intraluminal pressure and were induced either by (i) pre-ganglionic vagus nerve stimulation (PGS), (ii) stimulation of postganglionic intramural nerves via transmural stimulating electrodes (TMS) in the presence of ganglion-blocking concentrations of hexamethonium and (iii) application of exogenous acetylcholine (ACh). 3. The effect of phosphoramidon, which inhibits the breakdown of tachykinins, was investigated on ACh-, PGS- and TMS-induced contractions. Phosphoramidon (1-10 microM) facilitated contractions of the trachea induced by PGS, in a concentration-dependent manner, but had no effect on contractions of the trachea induced either by TMS or exogenous ACh. 4. The facilitatory effect of phosphoramidon (10 microM) on PGS-induced contractions was abolished by pretreating guinea-pigs with capsaicin 7 +/- 2 days before the in vitro experiments. Capsaicin pretreatment did not significantly alter responses to the spasmogens, ACh or substance P. Depletion of sensory neuropeptides, by capsaicin pretreatment was confirmed by the lack of response to capsaicin (1 microM) in vitro.(ABSTRACT TRUNCATED AT 250 WORDS)